A study on the service quality and consumers perception towards it / Shuhaniza Shamsul Khalil - Shamsul Khalil, Shuhaniza (1994)
Transportation, like any other industry requires efficient management because of its keen competition between the various transportation companies and at the same time each company is also in competition with other types of carriers. In order to survive in this competitive business, the company has to provide facilities that are better than other companies. Against these background, Executive Coach was launched on 16 th September 1993 to provide the necessary services to passengers emphasising on comfort, convenience, consistency, reliability and personal attention. Semai Impian Sdn Bhd, the company responsible for the Executive Coach, was given 72 travel permits by the authorities and is now using 10 out of the 72. Presently the company is only servicing users to Ipoh, Penang, Melaka and Johore Bahru. Its future plan is to expand its services to cover routes such as Alor Star, Perlis, Singapore, Kuantan, Trengganu and Kota Bharu. The study for this research covers only a period of five months that is from 1 st December 1993 to 30 th April 1994 and it is felt that for a better appraisal a longer period should be given. The analysis, however, can be accepted as a true picture of the Executive Coach's performance because the period under study include the peak and off- peak periods. Services provided by the Executive Coach are found to be satisfactorily and of high quality. Its survival to date proves that it is an efficiently managed transportation company , one that cares for the public and its workers.